Advances in Flow Modeling for Water Resources and Hydrological Engineering - Costanzo, Carmelina; Caloiero, Tommaso; Padulano, Roberta (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Water resource systems planning and management issues are often very complex. The pressures on water resources are increasing with the expanding scale of global development involving ecological and hydrological consequences in river basins and groundwater aquifers, and water-quality deterioration. All this leads to the increasing need for investigating the effects of different human influences and impacts on the hydrological regime and on water quality like as land-use changes, climatic variability and climate changes, and intensified water and land-use practices. The Special Issue "Advances in Flow Modeling for Water Resources and Hydrological Engineering" presents a collection of scientific contributions that provides a sample of the state-of-the-art and forefront research in this field. In particular, basin-wide water resources planning, watershed management, flood forecasting, droughts, climate change impacts on flood risk and water resources, reservoir operation and management, river morphology and sediment transport, river water quality, and irrigation were the main research and practice targets that the papers published in this Special Issue aimed to address.